Bridging Educational Gaps: Community Engagement in Rural Areas in Kuala Bangka - Shintia Putri Aisyah (EPISTEMOLOGI : JURNAL PENGABDIAN MASYARAKAT DAN PENELITIAN, 2024)
This study explores the role of community engagement in addressing educational disparities in rural areas, with a focus on Kuala Bangka, Indonesia. Using a qualitative descriptive method, data were collected through interviews, focus group discussions, observations, and document analysis. The findings reveal that local communities actively contribute to education through volunteer teaching, parental involvement, and collaborative support among stakeholders. These efforts have positively impacted students’ academic motivation, literacy development, and school participation. However, challenges such as limited resources, inconsistent participation, and lack of formal support remain significant barriers. The study concludes that while community-driven educational initiatives are effective, they require systemic support from educational authorities and institutions to be sustainable. This research emphasizes the importance of integrating community participation into national education strategies to ensure long-term and inclusive educational development in rural areas.